Advancing inclusive research calculator for oncology disease areas: A resource to support the development of enrollment targets in diversity action plans for industry sponsors. - David J Press; Spencer L James; Bruno Jolain; Nicole Richie (PLoS ONE)
Background The Food and Drug Omnibus Report Act, signed into law in 2022, requires industry sponsors to include diversity action plans in clinical study protocols. Defining reliable methodology for measures and benchmarks is critical to ensuring adequate and consistent representation of historically underrepresented patient populations in clinical trials. Methods We provide an Advancing Inclusive Research (AIR) Calculator, summary tables, and data query bank to support target setting for the development of diversity action plans and to take steps toward defining enrollment standards. The AIR Calculator uses data from the US Cancer Statistics database, which covers 100% of the US population. The database provides descriptive statistics for people diagnosed with 26 different cancers from 2015-2019 by cancer site, age at diagnosis, sex, and race and ethnicity, all stratified by stage at diagnosis (early, de novo metastatic, and combined). Descriptive characteristics include frequency counts, age-adjusted incidence rates, incidence rate ratios, and 95% CIs. Robustness test results are available in the data query bank by year of diagnosis. Results This resource offers insights into distributions of cancer in the US. The AIR Calculator allows users to calculate representative clinical study distributions based on the sponsor-designated study size. Discussion The AIR Calculator serves as a valuable resource for planning of clinical studies, but additional data analyses are necessary for a comprehensive understanding at the study level. Comprehensive data collection and alignment across industry are essential to ensure consistent, accurate, and transparent benchmarks in historically underrepresented patient populations and to track progress toward the goal of improving their representation in clinical research.